PENGARUH DUKUNGAN EMOSIONAL TERHADAP CAKUPAN KUNJUNGAN ANTENATAL CARE DI PUSKESMAS WAIPARE - Jefri, Johanes; Manongga, Stefanus P.; Dwi Wahyuni, Maria Magdalena; Picauly, Intje; R. Nayoan, Christina (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
The low coverage of antenatal care visits is attributed to a lack of emotional support from family, healthcare providers, community leaders, and religious figures. This study aims to analyze the impact of emotional support from various sources on the coverage of antenatal care visits in the working area of Puskesmas Waipare, Sikka Regency. The sources of emotional support include family, healthcare providers, community leaders, and religious figures. A quantitative cross-sectional study design was used, with a sample size of 83 pregnant women out of a total population of 104. The analysis involved bivariate analysis with simple logistic regression. The study found that emotional support from family significantly affects antenatal care visit coverage, with a p-value of 0.023 (<0.05) and an odds ratio (Exp(B)) of 6.462. Support from healthcare providers also had a significant impact, with a p-value of 0.027 (<0.05) and an odds ratio of 13.929. Support from community leaders showed a significant effect, with a p-value of 0.003 (<0.05) and an odds ratio of 15.400. Lastly, support from religious figures had a notable impact, with a p-value of 0.001 (<0.05) and an odds ratio of 20.000. The study concludes that emotional support from family, healthcare providers, community leaders, and religious figures significantly influences the coverage of antenatal care visits in the Waipare Health Center area.